Oxidative Stress and Protein Carbonylation in Adipose Tissue - Implications for Insulin Resistance and Diabetes Mellitus - Ruskovska, Tatjana (2013)
While historically considered simply as a depot for excess energy, white adipose tissue is a dynamically active endocrine organ capable of responding to a variety of efferent stimuli resulting in the synthesis and secretion of peptides, proteins and metabolites that serve as signal transducers to the peripheral and central circulation. Such regulation controls a variety of physiological processes including energy expenditure, food intake, reproductive capacity and responsiveness to insulin. Indeed, accumulation of inflammatory cells in white adipose tissue is considered to be causative in the development of insulin resistance and eventually type 2 diabetes mellitus. A large body of evidence suggests that oxidative stress in adipose tissue not only correlates with insulin resistance but is also causative in its development. Moreover, using the available plasma oxidative stress biomarkers, many clinical studies have shown the presence of systemic oxidative stress in obese insulin resistant subjects, and its decrease after the successful treatment of obesity. In this review we emphasize the role of protein carbonylation in dysfunctional obese white adipose tissue and its metabolic implications. We focus on glutathione S-transferase A4 as the key enzyme for trans-4-hydroxy-2-nonenal and trans-4-oxo-2-nonenal removal from the cell, thus preventing protein carbonylation.